The Eligibility of the Speaking-Skills Materials for 11th-grade Senior High School Students - Safitri, Dian; Dollah, Syarifuddin; Korompot, Chairil Anwar (Journal of Excellence in English Language Education, 2024)
The aims of this study are to determine the appropriateness of the English speaking-skills material with the criteria for good material established by Cunningsworth (1995) and Mukundan (2011). This research uses a qualitative approach with a qualitative descriptive research design. The subjects of this research were 11th-grade English materials at MAN 1 Maluku Tengah, an English teacher and seven 11th-grade students at MAN 1 Maluku Tengah. Data was collected using assessment checklists and interviews. The evaluation checklist was carried out offline at school and filled in by an 11th-grade English teacher and the researcher. Interviews with students are used to obtain information about students' needs regarding the English speaking-skill learning materials. Meanwhile, interviews with the teacher were conducted to obtain additional information regarding the English learning materials that she used. The research results show that the suitability of the English speaking-skills material with the overall criteria for good material is 86.15%. The highest percentage of criteria was “aims and approach”. The criteria have 95.8% because all the materials were in accordance with the learning objectives, syllabus and curriculum. Meanwhile, the lowest percentage of the criteria was “design and organization”. This is because the material is still lacking in design so the criteria just have 62.4%. From the research findings, the researcher concluded that the English speaking-skills material meets the standard criteria for good material by Cunningsworth (1995).